Anotaciones sobre la representación discursiva y autobiográfica del docente sanmarquino (caso: UNlVISM) - Vargas Morales, Zenon Eduardo (2007)
[he idenruv ofthe educationul collcge studeut, first of alt is modcled hy the J¡iSlO/'_\' ofthe universitv ihat has morked {he identitario developtnent ofthe se¡ olthe educational ones like individual people and lil;«social gmup in whom historically they llave developed. This history is the se! ofpolitical. ocademic. socia! circumstances that hove structured tlte minds o/ the educational oncs during their routine charactet; and which, somehow they //ClI'C structurcd a form 10 be, a certain tvpe ofidentiry like person and educational. The identitv is a crucial eletnent in lile l~'a_"of hov. rile (l11'¡¡professor» construct lile nutur« {~ír/¡ór activity, on how (he)' liv« hi« II'{/I'k subjcctivclv and tlu: ronditions of satisfaction and disstuisfaction.